Економічні погляди Михайла Грушевського - Заброварний, С. (Інститут історії України НАН України, 2008)
Hrushevsky’s economic views formed during his university studies and through his experience in European countries as positivistic conceptions of treating historic phenomena and processes. In historical research of economic growth he identifi ed three important factors: territory (land), peoples (labour), and cultural goods (accumulated capital), as well as domestic and external trade, enterprises, and initiative. In Ukrainian economic policy Hrushevsky saw the necessity of making use of an orientation towards the West and the Black Sea region, and in particular towards American achievements, for technical and social development.